2016
DOI: 10.1063/1.4950748
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-precision fabrication of 500 mm long and laterally graded Ru/C multilayer mirrors for X-ray light sources

Abstract: X-ray mirrors are needed for beam shaping and monochromatization at advanced research light sources, for instance, free-electron lasers and synchrotron sources. Such mirrors consist of a substrate and a coating. The shape accuracy of the substrate and the layer precision of the coating are the crucial parameters that determine the beam properties required for various applications. In principal, the selection of the layer materials determines the mirror reflectivity. A single layer mirror offers high reflectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…16,17 Ru has been used in multilayers in combination with Si as an analyser for polarization measurements 18 and with carbon and boron carbide as multilayer mirror in soft X-ray region 18 and as multilayer monochromators in hard X-ray region. 1,19 In the present work, we have studied Ru/C/Ru trilayer structure as a potential waveguide system for 8-to 20-keV X-ray energy regions. Carbon has been used as a barrier layer in multilayers to reduce interdiffusion at the interfaces and improve the reflectivity performance of the multilayers.…”
Section: X-ray Reflectivity (Xrr) Is a Well-established Technique For Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Ru has been used in multilayers in combination with Si as an analyser for polarization measurements 18 and with carbon and boron carbide as multilayer mirror in soft X-ray region 18 and as multilayer monochromators in hard X-ray region. 1,19 In the present work, we have studied Ru/C/Ru trilayer structure as a potential waveguide system for 8-to 20-keV X-ray energy regions. Carbon has been used as a barrier layer in multilayers to reduce interdiffusion at the interfaces and improve the reflectivity performance of the multilayers.…”
Section: X-ray Reflectivity (Xrr) Is a Well-established Technique For Surfacementioning
confidence: 99%
“…For X-ray optics applications, major challenge in the fabrication of multilayered systems is to achieve the precise thickness of all the layers. 1 In addition, film uniformity and interface quality is of paramount importance from application point of view. The quality of film and the interfaces formed by different layers are highly dependent on the deposition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The application of multilayer coating techniques to optical components of increasing size continues to make progress. Störmer et al [4] have reported the fabrication of a 500 mm long, laterally graded Ru/C multilayer mirror and its successful testing with Cu Kα 1 (8.048 keV) and Mo Kα 1 (17.48 keV) X-rays. The coating of silicon substrates with boron carbide has been carried up to a 1500 mm length by Störmer et al [5].…”
Section: Beamline Designmentioning
confidence: 99%
“…[9][10][11] At SPring-8, a compensation optical system was developed that uses a bimorph mirror to realize an ultimate beam size of 7 nm. In this work, the diffraction-limited operation was realized in a compensational way, although the employed multi-layer coated 12,13 Kirkpatrick-Baez (KB) mirrors [14][15][16][17][18][19] did not fully satisfy the Rayleigh criterion. 20 Furthermore, a two-stage focusing optical system was used at SPring-8 to change the beam size, in which diffraction-limited performances were realized at all beam sizes.…”
Section: Introductionmentioning
confidence: 99%